2021
DOI: 10.1002/adsc.202001611
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Intramolecular Decarbonylative Coupling of Aryl Selenol Esters

Abstract: This report describes a method for Ni‐catalyzed intramolecular decarbonylative coupling, which enables the conversion of areneselenol esters to diaryl selenides. The inexpensive and readily available catalyst can be employed under mild reaction conditions for the construction of structurally diverse diaryl selenides, including heterocyclic and natural product derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Methyl 4-((Phenylselanyl)carbonyl)benzoate (3ha). 32 Yield: 61% (58.6 mg) (using 12 equiv of H 2 SO 4 and HCOOH); yellowish solid; mp 133.0−134.5 °C; column chromatography (Hex/AcOEt95:5); 1 H NMR (400 MHz, CDCl 3 ): δ 8.15 (d,J = 8.1 Hz,2H),7.98 (d,J = 8.2 Hz,2H),2H),3H), 3.96 (s, 2H); 13 C{ 1 H} NMR (101 MHz,CDCl 3 ): δ 193.4,166.1,141.9,136.4,134.7,130.3,129.6,129.4,127.3,125.6,52.7 ppm. Se-phenyl 3-Cyanobenzoselenoate (3ia). Yield: 52% (44,6 mg) (using 12 equiv of H 2 SO 4 and HCOOH); white solid; mp 90.7−92.1 °C; column chromatography (Hex/AcOEt95:5); 1 H NMR (400 MHz, CDCl 3 ): δ 8.20 (s, 1H), 8.14 (d,J = 7.9 Hz,1H),7.89 (d,J = 7.6 Hz,1H),7.64 (t,J = 7.8 Hz,1H),2H),3H); 13 C{ 1 H} NMR (101 MHz,CDCl 3 ): δ 192.2,139.7,136.8,136.3,131.3,130.9,130.2,129.8,129.7,125.0,117.7,113.7 ppm; HRMS (ESI-TOF) m/z: [M + H] + calcd for C 14 H 9 NOSe, 287.9922; found, 287.9932.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Methyl 4-((Phenylselanyl)carbonyl)benzoate (3ha). 32 Yield: 61% (58.6 mg) (using 12 equiv of H 2 SO 4 and HCOOH); yellowish solid; mp 133.0−134.5 °C; column chromatography (Hex/AcOEt95:5); 1 H NMR (400 MHz, CDCl 3 ): δ 8.15 (d,J = 8.1 Hz,2H),7.98 (d,J = 8.2 Hz,2H),2H),3H), 3.96 (s, 2H); 13 C{ 1 H} NMR (101 MHz,CDCl 3 ): δ 193.4,166.1,141.9,136.4,134.7,130.3,129.6,129.4,127.3,125.6,52.7 ppm. Se-phenyl 3-Cyanobenzoselenoate (3ia). Yield: 52% (44,6 mg) (using 12 equiv of H 2 SO 4 and HCOOH); white solid; mp 90.7−92.1 °C; column chromatography (Hex/AcOEt95:5); 1 H NMR (400 MHz, CDCl 3 ): δ 8.20 (s, 1H), 8.14 (d,J = 7.9 Hz,1H),7.89 (d,J = 7.6 Hz,1H),7.64 (t,J = 7.8 Hz,1H),2H),3H); 13 C{ 1 H} NMR (101 MHz,CDCl 3 ): δ 192.2,139.7,136.8,136.3,131.3,130.9,130.2,129.8,129.7,125.0,117.7,113.7 ppm; HRMS (ESI-TOF) m/z: [M + H] + calcd for C 14 H 9 NOSe, 287.9922; found, 287.9932.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…9 Very recently, Xu, Yu, and coworkers realized the synthesis of various selenides by nickel-catalyzed intramolecular decarbonylative reaction of aryl selenoesters. 10 Also, Shao et al reported a nickel-catalyzed cross-electrophile coupling of aryl iodides and benzeneselenosulfonates 11 (Scheme 1b). These C-Se bond construction methods proceeded mainly under elevated temperature, in the presence of strong bases or stoichiometric amounts of metal reductant.…”
mentioning
confidence: 99%